Percutaneous coronary intervention in left main disease: SYNTAX, PRECOMBAT, EXCEL and NOBLE—combined cardiology and cardiac surgery perspective - Park, Duk-Woo; Ahn, Jung-Min; Park, Seung-Jung; Taggart, David P. (Annals of Cardiothoracic Surgery, 2018)
Although coronary-artery bypass grafting (CABG) is the standard choice of revascularization for significant left main coronary artery (LMCA) disease, percutaneous coronary intervention (PCI) for LMCA disease has been widely expanded with adoption of drug-eluting stents (DES). Several small- and moderate-sized trials of CABG and first-generation DES showed that PCI might be a good alternative for selected patients with LMCA disease. However, these early trials were relatively underpowered and comparative results of contemporary DES and CABG were clearly required. Subsequently, two large-sized trials comparing CABG and contemporary DES (EXCEL and NOBLE) were conducted, but these trials showed conflicting results with regards to the effects of PCI and CABG on clinical outcomes, which raises further uncertainty on the optimal revascularization for LMCA disease. This article serves to summarize the key findings of landmark clinical trials, to share our knowledge and experience and to express personal opinions on current controversies in the treatment of LMCA disease.